After-effects and disabilities in traffic crash victims in northern Brazil. (19th May 2017) - Rocha, Greiciane da Silva; Mello Jorge, Maria Helena Prado de; Grembek, Offer
ABSTRACT: Objectives : The objective of this study was to identify the characteristics related to crash and victim, as well as the after-effects/disabilities and consequences arising from traffic crashes occurring in the city of Rio Branco–Acre. Methods : This is an analytical descriptive cross-sectional study conducted in the City of Rio Branco–Acre. The study population consisted of 405 residents of the city who were victims of traffic crashes, of all age groups and genders, who were hospitalized for the first time as a result of the crash in public hospitals and the health system network, as recorded in the Hospital Information System, and who were discharged between January 1 and December 31, 2010. The data sources included hospital record consultations and active searches for the victims. Hierarchical logistic regression was performed to evaluate the factors associated with the after-effects. Results : The majority of the study population was motorcycle victims (68.6%), male, and young (20–39 years). Concerning the after-effects, the following were significantly associated: factors related to the presence of a postcrash activity limitation (odds ratio [OR] = 2.39; 95% confidence interval [CI], 2.39–6.76), length of hospital stay in days (OR = 1 03; 95% CI, 1.01–1.06), and surgical treatment (OR = 1.82; 95% CI, 1.03–3.21). Those who suffered damage to soft tissue and nerves or facial injury showed an odds ratio of 2 to 4 times of having an after-effect/disability, independent of the victim's personal attributes. Conclusion : The mechanism, such as the origin of the pattern of injuries, explains the exposure factors shown by each attribute of the victim and their characteristics. Many of the injuries were precursors to after-effects/disabilities, which, due to their nature and extent, result in the modification of the apparently healthy living standards of young victims who are routinely injured in traffic crashes. Therefore, public policies for prevention should be formulated, reformulated, and implemented, taking into account each attribute of the victims and their social conditions, because these are closely related to their habits and customs. This is a starting point for promoting changes to the current reality that traffic crashes present in the morbidity and mortality of the population.